Two new species of the genus Onchodellus (Acari: Pachylaelapidae) from China - Zhang, Xue-Song; Guo, Jian-Jun; Yi, Tian-Ci; Jin, Dao-Chao (Zootaxa, 2020)
This paper describes two new species of the family Pachylaelapidae, Onchodellus menglaensis sp. nov. and O. quattuorspinous sp. nov., from the earth-boring dung beetles, Enoplotrupes sinensis Hope (Scarabaeoidea: Geotrupidae), collected from Mengla County, Yunnan Province, China. An identification key to the Chinese species of the genus Onchodellus (females) is provided.